Vocational rehabilitation service usage and outcomes for individuals with Autism Spectrum Disorder - Nye-Lengerman, Kelly (Research in autism spectrum disorders, 2017)
In the pursuit of improving employment outcomes for individuals with Autism Spectrum Disorder (ASD), understanding how participants are using Vocational Rehabilitation (VR), and which services result in competitive integrated employment is of great interest to advocates, families, professionals, and policy makers. The primary objective of this study was to examine the relationships between participant characteristics, service delivery, and employment outcomes for individuals with ASD in state VR programs. The Rehabilitation Services Administration's Case Service Report (RSA-911) database for fiscal year 2013 was examined using a binary logistic regression analysis to explore ASD characteristics and service variables. Results indicate that ASD characteristics, defined as a source of impairment by VR, had predictive capacity for administrative VR services participants received (e.g. assessment and vocational rehabilitation counseling and guidance (VRCG)), but not for job-related services (e.g. job search, job placement, and on-the-job supports). In addition, job-related VR services were more likely to be associated with integrated employment at closure as compared to administrative VR services. In some cases, additional variables related to gender, race, and state system decreased the likelihood of a VR recipient receivingspecific services or achieving integrated employment. Discussion includes how awareness of service access and equity can assist in improving the quality and outcomes of VR services.